(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article analyzes the scientific and practical issues of regulation of social networks, in particular, the issues of the need for legal regulation of social networks in the context of digital development of the Republic of Uzbekistan. Scientific novelty of research consists in the fact that the article was first explored the issues of forming legal basis of social networks, the regulation of relations in social networks, protection of rights and freedoms, interests of legal entities and the state of information security. The study is considered important from the point of view of the fundamental study of legal relations in social networks in Uzbekistan. The practical significance of this article is the possibility of using the results obtained in the course of the study in the implementation of the tasks provided for in the Laws of the Republic of Uzbekistan «On Informatization», «On the principles and guarantees of freedom of Information», «On Guarantees and freedom of access to information».